Co-integration between Corruption and Economic Growth through Investment Channels: Empirical Evidence using the ARDL Bound Testing Approach for the Tunisian Case - Akrout, Zied; Bachouch, Hamid; Moualdi, Salim (International Journal of Economics and Financial Issues, 2021)
This study examines the relationship between corruption and economic growth in Tunisia from 1992 to 2018 by focusing on the role of the discretionary power and the distortion of the public spending. To explore the relationship between the variables of interest, the ARDL Bound testing co-integration approach of Pesaran and Shin (1999) was used. The empirical results showed that corruption negatively affects the long-term economic performance by suggesting that large-scale public investment is not necessarily desirable in an environment characterized by corruption as this leads to the waste of public funds. However, the estimation of an ECM model of short-term dynamics shows that corruption is associated with the increase of the real GDP per capita. Therefore, these results support the idea that corruption undermines long-term economic performance and call for institutional reforms to improve the quality of governance as a pre-condition for any broad-based economic growth. Keywords: Corruption, Economic Growth, Investment, Co-integration, ARDL, ECM. JEL Classifications : D73, O4, E22, C12, C15 DOI: https://doi.org/10.32479/ijefi.10879